Idiopathic mesenteric phlebosclerosis: a rare but important disease in Asian populations - Xiao-Tong Hu; Dong Wang (European Journal of Medical Research)
Abstract Idiopathic mesenteric phlebosclerosis (IMP) is a rare form of ischemic colitis that predominantly impacts Asian populations. Despite some recognizable signs, there is a significant lack of awareness about IMP. In this review, we explore the etiology, pathogenesis, imaging manifestations, endoscopic traits, and therapeutic modalities of IMP. In addition, we discuss the deficiencies in the current comprehension of IMP and the potential research orientations in future.